Hostage spaces of the contemporary Islamicate world phantom territoriality - Lukic, Dejan (Suspensions : contemporary Middle Eastern and Islamicate thought, 2013)
Gripping expose of the act of hostage-taking, and of being a hostage, in the spheres of war and terrorism in post-communist geographies of global Islam.